‘It's all about the preparation’. Virtual reality courtroom for survivors of sexual violence: a case study - Jónsdóttir, Erla Katrín (Psychology, crime & law, 2025)
This exploratory case study examined the effect of virtual reality exposure therapy (VRET) for a survivor of sexual violence (SV) as a preparation for a court hearing. Five sessions of VRET were completed before the court hearing, and one follow-up session was completed after the trial. In-depth interviews were conducted after each session for detailed assessment about the effects of therapy and first-hand experience of preparing for court. The participant said that the VRET sessions helped her prepare for court, gave an increased sense of control, and allowed her to manage emotions and bodily reactions. The trial itself and preparing for it was seen as an important part of the recovery process, where social support played an important role. VRET appears to be a promising preparation method for SV survivors taking their cases to court. More research is needed to standardize and improve the quality of VRET and examine how it can be combined with other sources of support.